Resiliencia en madres de hijos con discapacidad intelectual - Carmona García, Lilia Susana (2026)
The objective was to explore and describe the resilience in mothers of children with intellectual Disability (ID). A quantitative, non-experimental, exploratory, descriptive and transectional study was conducted. Ninety-two mothers of individuals who with ID in an institution that offers training service to children with any ID, participated. The results shows that general resilience levels were high ranking at 89% self-determination ranked in 90%, 83% had a high level of hope, 91% showed a very high level of adaptation with personal responsibility, 74% felt that the help of their partners is fair and favorable, 64% thought that they satisfy the needs of their children with ID. A significant correlation (p< .05) was also found between Resilience, Self-determination, Hopelessness, and adaptation with personal responsibility with the mother’s Education; as well as between Hopelessness and Limited Resources with the mother’s Age. In conclusion, these women fall on the category of resilience, and they have the ability to face the adversity of taking care of their children with ID and have factors of resilience.